Wireless Technologies 2012
DOI: 10.4018/978-1-61350-101-6.ch308
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Spatial Awareness by Integrating Internet Geographic Information Services (GIServices) with Real Time Wireless Mobile GIS Applications

Abstract: Spatial awareness is one of the fundamental decision making capabilities for human beings. Two key information technologies, Internet Geographic Information Services (GIServices) and wireless mobile Geographic Information Systems (GIS) can enhance the spatial awareness of decision makers and facilitate more efficient and comprehensive decision making processes. Internet GIServices provide a collaborative communication environment for sharing data, information and knowledge among multiple decision makers and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Koko et al, (2014) in their study on real-time geospatial data collection and visualization using smart-phone observed that, while the pen and paper method has been the traditional way to collect monitoring data in the field, with the expanding availability and functionality of powerful hand held computers, GPS, and mobile GIS, researchers are increasingly integrating and replacing conventional field methods with more efficient mobile methods. The study found out that a distributed GIS has seen recent GIS technologies dramatically depart from the traditional two-tier client-server model, to mobile to web technologies that has in turn improved project performance, by strengthening monitoring and evaluation system (Peng & Tsou, 2003). Both of these studies were focused on data collection, as compared to information use for decision making.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Koko et al, (2014) in their study on real-time geospatial data collection and visualization using smart-phone observed that, while the pen and paper method has been the traditional way to collect monitoring data in the field, with the expanding availability and functionality of powerful hand held computers, GPS, and mobile GIS, researchers are increasingly integrating and replacing conventional field methods with more efficient mobile methods. The study found out that a distributed GIS has seen recent GIS technologies dramatically depart from the traditional two-tier client-server model, to mobile to web technologies that has in turn improved project performance, by strengthening monitoring and evaluation system (Peng & Tsou, 2003). Both of these studies were focused on data collection, as compared to information use for decision making.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…LMT is defined as two parts consisting of Info and Attribute in (1). LMT = {Info, Attribute} (1) Info contains the basic information of the Node, includes Geo and Description in (2).…”
Section: Problem Statement and Approachmentioning
confidence: 99%
“…Mobile GIS has two major application areas, one is Field-based GIS, and the other is Location-based Services (LBS). Field-based GIS focus on the GIS data collection, validation and update, while Location-based Services focus on business-oriented location management functions [1]. This paper will focus on the second area, the authors don't need to change the original GIS data sets, but just use them as reference maps.…”
Section: Introductionmentioning
confidence: 99%
“…Internet GIServices are network-based geographic information services which utilize both wired and wireless Internet functionality to access geospatial information, spatial analytical tools, and GIS web services (Tsou, 2009). The GIS community started to research on-line, web-based, and distributed GIServices in the mid-1990s (Gardels, 1996;Plewe, 1997;Tang, 1997, Peng & Tsou, 2003.…”
Section: Collaborative Decision Makingsmentioning
confidence: 99%